1997
DOI: 10.5694/j.1326-5377.1997.tb126656.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of an automated up‐timer for measurement of mobility in older adults

Abstract: Objective: To test the reliability, validity and utility of an "up-timer", an automated device to measure time spent standing and walking.Design: Repeat measurement of mobility one week apart in a convenience sample. Setting: Hostel and nursing homes in Melbourne.Participants: 26 hostel and 24 nursing home residents (aged 70-99 years) participated. They were mobile, with or without the use of walking aids or personal assistance. Outcome measures:"Up-time" (measured with the up-timer); functional activity (meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…26 It has also been used in the setting of a nursing home/hostel where it showed good correlation with the Functional Independence Measure (r = 0.78) and the Barthel Index (r = 0.80). 27 …”
Section: Evaluation Of Mood Cognition and Other Functional Charactementioning
confidence: 97%
“…26 It has also been used in the setting of a nursing home/hostel where it showed good correlation with the Functional Independence Measure (r = 0.78) and the Barthel Index (r = 0.80). 27 …”
Section: Evaluation Of Mood Cognition and Other Functional Charactementioning
confidence: 97%
“…3 The single mercury tilt switch in units used in the previous study was replaced by three mercury tilt switches, which sensed the three-dimensional position of the thigh relative to gravity. This modi cation ensured that there was no possibility of false recordings of uptime when a person was not upright.…”
Section: Equipmentmentioning
confidence: 99%
“…Uptime provides new information about a patient's response to rehabilitation that complements other outcome measures currently in use. 3 In patients with chronic pain it has been shown that as uptime increases there is a corresponding decrease in symptoms of pain and an improvement in functional capacity. 1,2 However, no research to date has reported the measurement of uptime in children.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations